Effects of Yanang (Tiliacora triandra) Gum on Gelation of Waxy Rice Flour - Samutsri*, Wisutthana; Thimtuad, Sujittra (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Crude hydrocolloid extract has been prepared from the leaves of Yanang (Tiliacora triandra). This research studied effects of Yanang gum on pasting and textureal properties of blending of waxy rice flour. Rapid visco analysis (RVA) results showed that the ratio of Yanang extract to water of 1:3 and 1:4 (w/w) significantly decreased the trough, breakdown, and final viscosities of the waxy rice flour whereas the peak viscosities, peak time, and pasting temperatures of the blends were increased. Textural study revealed that the addition of crude Yanang gum enhanced more hardness and springiness of the blending gels than those of waxy rice flour gel, whereas cohesiveness was less affected. These results would be useful as a guideline for developing frozen starch-based food products containing crude Yanang gum. Keywords: Yanang, hydrocolloid, waxy rice flour, pasting properties, textural properties, RVA Corresponding author: Tel.: 08-1899-7447 Fax: 0-2522-6609 E-mail: iwisut.s@gmail.com